2017
DOI: 10.1136/emermed-2016-206323
|View full text |Cite
|
Sign up to set email alerts
|

Mountain rescue cardiopulmonary resuscitation: a comparison between manual and mechanical chest compressions during manikin cardio resuscitation

Abstract: Manual chest compression is possible on a snowmobile during transport even in challenging terrain. This experimental study shows that high-quality chest compressions and manual ventilation can be performed in an intubated patient during a short-term transportation on a sledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…During transportation in an alpine setting, this seems to be only feasible using mechanical chest compression devices. Feasibility of this has been shown previously in the urban/flat rural setting [ 12 ]. The findings in our current study suggest that high quality mechanical chest compressions during an alpine rescue mission are achievable.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…During transportation in an alpine setting, this seems to be only feasible using mechanical chest compression devices. Feasibility of this has been shown previously in the urban/flat rural setting [ 12 ]. The findings in our current study suggest that high quality mechanical chest compressions during an alpine rescue mission are achievable.…”
Section: Discussionmentioning
confidence: 78%
“…Our results complement the findings of one previous study, in which mechanical CPR in alpine terrain was investigated. Thomassen et al [ 12 ] report high quality of both manual and mechanical chest compressions during transportation on a sledge. Compared to our study, the scenario of this study was however much less representative for the reality of alpine rescue organizations, as mentioned before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including staff from ICU-related units has been found to be an efficient use of human resources and time, to ensure that the MET arrives at the calling site within the target of 5 minutes, as rescue performance metrics for CPR are limited to 5 minutes. 16 Some studies have evaluated the performance of general ward staff with respect to activating an RRS when the triggering criteria are fulfilled; study findings have revealed a wide variation in the rate of delayed activation (21%-81%). [17][18][19] We should mention that not all patients need to be treated within 5 minutes, for example, a patient at risk of a suicide attempt.…”
Section: Regional Rrs Administrationmentioning
confidence: 99%
“…It follows that manual compression of the chest is possible on a snowmobile during transport, even in difficult terrain. This experimental study shows that high-quality chest compressions and manual ventilation can be performed on a patient intubated during short-term toboggan transport (Thomassen, Skaiaa, Assmuss, Østerås, Heltne, Wik, and Brattebo, 2017).…”
Section: Scientific Research In the Area Of Emergency Medical Servicesmentioning
confidence: 92%